การพัฒนาบทเรียนร่วมกันของครูเพื่อเสริมสร้างสมรรถภาพการจัดการเรียนการสอนภาษาไทย และความสามารถทางการอ่านของนักเรียนประถมศึกษาตอนต้น ของโรงเรียนวัดทางหลวง (เทพราษฎร์รังสรรค์) - เขียวหวาน ธนัชชา; ลัญฉวรรธนะกร ฉัตรวรรณ์ (An Online Journal of Education, 2018)
The purposes of this research were 1) to enhance Thai language teachers’ instructional competencies, 2) to develop lower elementary school students’ reading abilities, and 3) to investigate the students’ learning behaviors of Watthangluang (Tepparatrangsan) school through lesson study. According to research conducted by following Lesson Study (LS) concept, the researcher utilized practical action research as the research method. Participants were three teachers teaching Thai subject and forty students at lower elementary school level. The data were collected from observation, interviewing, and reading test. The research findings were as follows: 1) Teachers developed their instructional competencies in designing their instructions appropriately, and having better understanding about curriculum requirements, content knowledge, teaching methods, students’ learning, instructional media implementing, and learning assessment. 2) After conducting the lesson study process, students had the mean scores of reading abilities higher than earlier across all grade levels. And 3) Students showed good learning behaviors i.e. learning activity participation, enthusiasm for learning, answering the teacher’s questions and finally they had more positive attitude toward reading in Thai language.